2012
DOI: 10.1038/nature10845
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal plasticity is necessary for learning intentional neuroprosthetic skills

Abstract: The ability to learn new skills and perfect them with practice applies not only to physical skills but also to abstract skills1, like motor planning or neuroprosthetic actions. Although plasticity in corticostriatal circuits has been implicated in learning physical skills2–4, it remains unclear if similar circuits or processes are required for abstract skill learning. We utilized a novel behavioral paradigm in rodents to investigate the role of corticostriatal plasticity in abstract skill learning. Rodents lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
341
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(373 citation statements)
references
References 31 publications
28
341
2
2
Order By: Relevance
“…Functional and structural changes in the dorsomedial striatum have been shown to be associated with the early phase, whereas such changes in the dorsolateral striatum have been shown to be associated with the late phase. Recently, similar changes have been observed in neurofeedback learning in animals 45 and humans 85 (FIG. 2), providing support to this theory.…”
Section: Skill Learningsupporting
confidence: 48%
See 3 more Smart Citations
“…Functional and structural changes in the dorsomedial striatum have been shown to be associated with the early phase, whereas such changes in the dorsolateral striatum have been shown to be associated with the late phase. Recently, similar changes have been observed in neurofeedback learning in animals 45 and humans 85 (FIG. 2), providing support to this theory.…”
Section: Skill Learningsupporting
confidence: 48%
“…The specificity of the trained neural substrate was first noted in a study involving non-human primates 44 , which showed that the regulation of single-cell firing in the motor cortex could be learned. The local specificity of learned physiological regulation at the microscopic level was later confirmed by a series of impressive experiments in which rats were rewarded for increasing the firing rate of a cell in the motor cortex and simultaneously decreasing the firing rate of an adjacent cell 45 . Another study in rats showed that neurofeedback could be used to induce selective temporal coherence between neurons in M1 and in the dorsal striatum 46 .…”
Section: Adaptive Neurofeedbackmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, comparing veritable feedback with no feedback , inversely proportional feedback , or feedback from a distinct brain region (Paret et al, 2014), revealed similar neural changes from baseline to the first trial in both experimental and control groups. On the other hand, findings from both human and animal studies suggest that explicit techniques are unnecessary and that contingent feedback alone is responsible for neural regulation (Caria et al, 2010;Koralek, Jin, Long, Costa, & Carmena, 2012). Thus, the degree to which explicit mental strategies relate to learned brain modulation remains unclear.…”
Section: Fmrimentioning
confidence: 99%